2022
DOI: 10.1111/bjh.18052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conditioning regimen intensity on the outcomes of peripheral T‐cell lymphoma, anaplastic large cell lymphoma and angioimmunoblastic T‐cell lymphoma patients undergoing allogeneic transplant

Abstract: Summary There have been no large studies comparing reduced‐intensity/non‐myeloablative conditioning (RIC/NMA) to myeloablative conditioning (MAC) regimens in T‐cell non‐Hodgkin lymphoma (T‐NHL) patients undergoing allogeneic transplant (allo‐HCT). A total of 803 adults with peripheral T‐cell lymphoma, anaplastic large cell lymphoma and angioimmunoblastic T‐cell lymphoma (age 18–65 years), undergoing allo‐HCT between 2008–2019 and reported to the Center for International Blood and Marrow Transplant Research wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This is similar to a previous study in T‐cell NHL (not limited to ALCL) from the Société Francophone de Greffe de Moelle et de Thérapie Cellulaire (SFGM‐TC) of 285 patients who underwent allo‐HCT for PTCL 36 . In addition, Savani et al 13 reported similar findings in a recently published CIBMTR analysis. The 5‐year OS, PFS and NRM were not different in the patients who received RIC/NMA versus those who received MAC, while the risk of Grade 2–4 GVHD was higher in the MAC cohort.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is similar to a previous study in T‐cell NHL (not limited to ALCL) from the Société Francophone de Greffe de Moelle et de Thérapie Cellulaire (SFGM‐TC) of 285 patients who underwent allo‐HCT for PTCL 36 . In addition, Savani et al 13 reported similar findings in a recently published CIBMTR analysis. The 5‐year OS, PFS and NRM were not different in the patients who received RIC/NMA versus those who received MAC, while the risk of Grade 2–4 GVHD was higher in the MAC cohort.…”
Section: Discussionsupporting
confidence: 89%
“…12 Adoptive immunotherapy in the form of allogeneic HCT (allo-HCT) is a potentially curative treatment for patients with select R/R T-cell lymphomas. [13][14][15] In fact, with the recent decreased utilisation of allo-HCT in diffuse large B-cell lymphoma, T-cell NHL has now become the most common indication of allografting for lymphomas in the United States. [14][15][16] However, the role of allo-HCT in R/R ALCL is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Developing chimeric antigen receptor T cell therapy has remarkably changed the landscape of relapsed and refractory lymphoma, especially diffuse large B cell lymphoma; however, approximately 60% of patients ultimately experience relapse, and the median PFS was only 5.9 months in the ZUMA-1 trial, which confirmed the efficacy of axicabtagene ciloleucel in patients with relapsed and refractory large B cell lymphoma [ 38 40 ]. Allogeneic HCT continues to play an important role in patient management; therefore, further developments are needed to improve outcomes, and the results of allogeneic HCT in patients with NHL in this study and previous studies are inadequate [ 14 , 18 , 29 , 31 34 ]. As suggested in our study, it may be useless to rely on simply increasing conditioning of patients with NHL.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, several retrospective studies of patients with myelodysplastic syndromes reported no statistically significant differences in relapse and OS between RIC and MAC [ 12 , 13 ]. Regarding patients with NHL, RIC has a similar or higher OS compared with that of MAC [ 14 , 18 , 29 , 31 34 ]; however, only a few studies have compared the effects of simple antitumor drug volumes with Flu/Bu2 and Flu/Bu4. The largest retrospective study from the European Society for Blood and Marrow Transplantation compared Flu/Bu2 and fludarabine plus a myeloablative dose of busulfan (Flu/Bu3/4) in patients from a cohort consisting of approximately 90% chemosensitive NHL patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…39 PB allografts have also been associated with reduced risk of relapse and improved survival in patients with Hodgkin lymphoma who underwent alloBMT with RIC. 40 While some studies have found no association between graft source and survival outcomes in PTCL, 28 source may be in uenced by conditioning regimen, 41 donor selection, 28 and histology/disease characteristics. 26 In our study, all patients received NMA conditioning with PTCy, regardless of histology or other clinical features.…”
Section: Discussionmentioning
confidence: 99%